Larval description and chaetotaxic analysis of Dineutus sinuosipennis Laporte, 1840, with a key for the identification of larvae of the tribe Dineutini (Coleoptera, Gyrinidae) - Mariano C. Michat; Grey T. Gustafson; Johannes Bergsten (ZooKeys, 2017)
The larvae of the Malagasy whirligig beetle Dineutus sinuosipennis Laporte, 1840, identified using DNA sequence data, are described and illustrated for the first time, including detailed morphometric and chaetotaxic analyses of selected structures and a description of larval habitat. Larvae of the genus Dineutus Macleay, 1825 are diagnosed, and a key to identify the genera of the tribe Dineutini is presented. Larvae of Dineutus exhibit the characters traditionally recognized as autapomorphies of the Gyrinidae: body less sclerotized, egg bursters located on the parietal, one additional sensorial plate on the third antennomere, cardo and lacinia well developed, prementum completely divided, abdominal tracheal gills, and four terminal hooks on the pygopod. They also share with larvae of the other Dineutini genera these putative synapomorphies: numerous minute pore-like additional structures on the ultimate maxillary and labial palpomeres, coxal primary seta CO12 inserted submedially, and trochanteral primary seta TR2 absent. Larvae of Dineutus can be distinguished from those of other known genera of Dineutini by the posterior margin of the lacinia not dentate, tracheal gills plumose, parietal seta PA5 inserted relatively far from setae PA7–9, mandibular pores MNb and MNc inserted relatively far from each other, and tarsal seta TA1 inserted submedially.